A Case of "Cryptammonia": Disseminated Cryptococcal Infection Generating Profound Hyperammonemia in a Liver Transplant Recipient. (October 2022) - Phillips, Steven M.; Pouch, Stephanie M.; Lo, Denise J.; Kandiah, Sheetal; Lomashvili, Koba A.; Subramanian, Ram A.; Moran, Peter; Killian, Alley; Kandiah, Prem A.
Mycoplasma and Ureaplasma infections have been described as a cause of hyperammonemia syndrome leading to devastating neurological injury in the post-transplant period, most commonly in lung transplant recipients. The occurrence of significant hyperammonemia caused by other urease-producing organisms remains unclear. We describe a case of disseminated cryptococcosis presenting with profound hyperammonemia in a 55-year-old orthotopic liver transplant recipient. Through a process of elimination, other potential causes for hyperammonemia were excluded revealing a probable association between hyperammonemia and disseminated cryptococcosis.